Comorbilidad y factores pronósticos al ingreso en una cohorte COVID-19 de un hospital general - Martos Pérez, F. (Rev Clin Esp, 2021)
ANTECEDENTS AND OBJECTIVE: To describe clinical features, comorbidity, and prognostic factors associated with in-hospital mortality in a cohort of COVID-19 admitted to a general hospital. MATERIAL AND METHODS: Retrospective cohort study of patients with COVID-19 admitted from 26th February, who had been discharged or died, up to 29th April, 2020. A descriptive study and an analysis of factors associated with intrahospital mortality were performed. RESULTS: Out of the 101 patients, 96 were analysed. Of these, 79 (82%) recovered and were discharged, and 17 (18%) died in the hospital. Diagnosis of COVID-19 was confirmed by polymerase chain reaction to SARS-CoV-2 in 92 (92.5%). The mean age was 63 years, and 66% were male. The most frequent comorbidities were hypertension (40%), diabetes mellitus (16%) and cardiopathy (14%). Patients who died were older (mean 77 vs 60 years), had higher prevalence of hypertension (71% vs 33%), and cardiopathy (47% vs 6%), and higher levels of lactate dehydrogenase (LDH) and reactive C protein (mean 662 vs 335 UI/L, and 193 vs 121 mg/L respectively) on admission. In a multivariant analysis the variables significantly associated to mortality were the presence of cardiopathy (CI 95% OR 2,58-67,07), levels of LDH ≥ 345 IU/L (CI 95% OR 1,52-46,00), and age ≥ 65 years (CI 95% OR 1,23-44,62). CONCLUSIONS: The presence of cardiopathy, levels of LDH ≥ 345 IU/L and age  ≥ 65 years are associated with a higher risk of death during hospital stay for COVID-19. This model should be validated in prospective cohorts.